In Vitro and In Vivo Interventions Reveal the Health Benefits of Levan-Type Exopolysaccharide Produced by a Fish Gut Isolate Lactobacillus reuteri FW2 - Waqar Ahmad; Anam Nasir; Satya Prakash; Azam Hayat; Mujaddad ur Rehman; Shazia Khaliq; Kalsoom Akhtar; Munir Ahmad Anwar; Nayla Munawar (Life)
Microorganisms synthesize diverse types of exopolysaccharides (EPSs). EPSs with varying structural and physical properties can demonstrate unique health benefits, which allow for their tailored applications as functional foods such as prebiotics. Levan, a fructose-based EPS, is gaining considerable attention as an effective prebiotic to support the growth of beneficial gut bacteria. Consequently, this enhances digestive health, boosts the immune system, and reduces the risk of chronic diseases. Unfortunately, limited studies are available on levan-type EPSs to demonstrate their role as prebiotics. Therefore, in this study, we conducted in vitro and in vivo experiments, concerning intestinal cell integrity and metabolic syndrome, to assess the therapeutic potential of levan derived from Lactobacillus reuteri FW2. The in vitro experimental results revealed that levan improved the survival of impaired HT-29 epithelial cells of the intestine and also exerted antioxidant effects. In the in vivo experiments, mice fed with levan-supplemented feed exhibited low body weight gain, blood glucose, and serum cholesterol levels compared to the control group. These findings highlight the biotherapeutic potential of L. reuteri FW2-derived levan for improving metabolic syndrome and its associated aspects. It also signifies the need for a further detailed investigation based on clinical trials to include levan in dietary supplements for improved health and well-being.